A prediction model of surface heat transfer coefficient in insulating packaging with phase change materials. (June 2020) - Pan, Liao; Chen, Xi; Lu, Lixin; Wang, Jun; Qiu, Xiaolin
Graphical abstract: Highlights: A semi-infinite phase change model combined with an iterative method to solve the coupling parameters of surface heat transfer coefficient and temperature field was proposed. Based on the semi-infinite phase change model, the key affecting parameters of surface heat transfer coefficient were discussed. A concise surface heat transfer coefficient prediction model involved the key affecting parameters of surface heat transfer coefficient was also developed for engineering application. Abstract: Surface heat transfer coefficient is one of the crucial parameters for determining the system thermal resistance of insulating packaging. However, the surface heat transfer coefficient which couples with the temperature field in insulating packaging is difficult to experimentally measure and independently calculate. In this study an iterative method based on a semi-infinite phase change model was proposed to solve the coupling parameters of surface heat transfer coefficient and temperature field. Then, the semi-infinite phase change model curves were compared with classic Neumann model and Mehling model. Furthermore, the affecting parameters of surface heat transfer coefficient were discussed through this semi-infinite phase change model, and a concise prediction model of surface heat transfer coefficient was also developed for engineering application. Finally, this concise prediction model was verified by "Ice Melting Method". The results indicate that the proposed semi-infinite phase change model and iterative method can simultaneously calculate the coupling parameters of surface heat transfer coefficient and the temperature field in insulating packaging, and show a consistent with the classic Neumann model and Mehling model. The key parameters of surface heat transfer coefficient include the thickness and thermal conductivity coefficient of insulating wall, and the excess temperature also significantly influences the surface heat transfer coefficient. Furthermore, the system thermal resistance calculated by the novel concise prediction model has a good agreement with the experimental data of "Ice Melting Method" presented by Burgess.